Sustainable leadership best practices in enhancing business resilience and performance of robusta coffee farmers - Tanti Sugiharti (Journal of Enterprise and Development (JED), 2023)
Purpose — This research aims to demonstrate the best practices of sustainable leadership in the creation of business resilience.Method — This is qualitative research with a descriptive method. The researcher conducted semi-structured interviews with six participants in North Lombok using purposive sampling, as well as observed post-harvest Robusta coffee products.Result — The sustainable leadership practices found in this research are innovation, social responsibility, environmental responsibility, and ethical behavior. These are needed to empower and increase business resilience and performance. Furthermore, greater opportunities for community benefit and environmental sustainability can be achieved through these practices.Contribution — Current research on how sustainable leadership theory can affect the practices of small and medium enterprises is still inadequate, with insufficient studies available. This study addresses the gap by showcasing several best practices of sustainable leadership demonstrated by coffee SMEs in North Lombok and enhancing the emerging sustainable leadership theory in this area.